Study of Funding for Special Education Programs. Report to the 67th Session of the Nevada Legislature. Bulletin No. 93-25 - Botts, Jeanne; Nevada Legislative Counsel Bureau, Carson City. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1992)
This study of the financing of special education programs for children with disabilities or giftedness/talent was mandated by the legislature of Nevada to: (1) examine the amount of federal, state, and local money expended for special education programs and the proportion of total funding for special education programs provided from each source; (2) determine the actual costs of providing special education programs; (3) analyze the feasibility of funding special education programs on the basis of class size or by pupil-teacher ratios; and (4) review methods used in other states to fund special education programs. The report's sections cover: history of special education laws, number and placement of students with disabilities; federal, state, and local funding for special education; actual special education program costs; alternative funding mechanisms for special education; and programs for gifted/talented students. Findings are presented in both text and 29 tables. Key findings include, among others: special education is generally twice as expensive as the average cost per pupil for regular education; disabled students make up 7.95 percent of Nevada's school population; 44 percent of special education students are educated in resource rooms, while 34 percent are served within their regular classrooms; and 4.6 percent of all students were enrolled in programs for gifted/talented students in fiscal year 1992-93, up from 3.6 percent in 1990-91. (Contains 29 references.) (JDD)
Availability: Publications Section, Legislative Counsel Bureau, Legislative Building, Capitol Complex, Carson City, NV 89710 (no charge).
Policymakers.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Disabilities; Educational Legislation; Elementary Secondary Education; Federal Aid; Federal Legislation; Financial Support; Funding Formulas; Gifted; Incidence; Program Costs; School Funds; Special Education; State Aid; State Legislation; Student Placement; Talent; Nevada; Reports, Evaluative